Daily spiritual experience in Indonesian elite athletes: able-bodied and disabilities - Sofyan, Davi (COUNS-EDU: The International Journal of Counseling and Education, 2021)
Spirituality is the individual's belief in the existence, presence and involvement of transcendent divine beings in everyday life. This belief is accompanied by activities that aim to get closer to the transcendent figure (God). The aim of this research is to describe the level of daily spiritual experience in the elite able-bodied athletes and with disabilities, compare the spiritual experience level of the elite athletes of able-bodied and with disabilities, describe the socio-demography of elite athletes able-bodied and with disabilities. To support the study, we used a descriptive analysis method of 10 elite athletes consisting of five elite athletes with able-bodied athletes and five elite athletes with disabilities. The Daily Spiritual Experiences Scale was used in this study to measure daily spiritual experiences. The univariate test model was used to test the relationship between sociodemographic factors and the Daily Spiritual Experiences Scale score. The results show that of the 10 respondents have a different average score of daily spiritual experiences. Five able-bodied athletes show a very high spiritual level, while two athletes with disabilities exhibit a very high spiritual level and three people with a high spiritual level. Further research is needed to conduct in-depth studies related to the Daily Spiritual Experience in athletes by combining and analyzing quantitative and qualitative data.